The challenge of screen mediated shared reading for children’s learning and engagement - Read, Kirsten; Harrison, Hayley; Mireku, Brianna; Ying, Katrina (Frontiers in Psychology, 2023)
Introduction Screen mediated shared reading (SMSR), which involves an adult reading a child a book through video-chat, is a recent development in shared reading. In this study, we investigated whether, as in in-person shared reading, children could learn new words from SMSR, and whether having a physical copy of the book to follow along with impacted children’s novel word retention and engagement in this setting. Method Three- to 5-year-old participants (n = 34) were read an 8-page rhyming, “Meet the Friendly Monsters” story by a researcher over Zoom, via screen sharing an e-version of the story used in previous studies. Participants were randomly assigned to one of two conditions: SMSR with or without a paper copy of the book to follow along with. The session was recorded to measure children’s engagement behaviors during the reading. Novel word learning from the story was measured with both a multiple choice identification test and a monster naming test, both administered immediately after the initial reading, then re-administered 10–14 days later. Engagement during the SMSR sessions was measured every 30-s on a scale of 1 (low engagement) to 5 (high engagement), and then averaged for each child. Results Results show that children overall performed slightly above chance on novel monster name retention from the SMSR. However, retention was not as strong as seen in other in-person shared reading studies using the same story. Additionally, while children remembered monster names with equal efficacy regardless of condition and level of engagement, there were still qualitative differences in the reading sessions depending on whether children had their own paper copy of the book to follow along with – in general, the ‘with book’ condition appeared to increase the challenges posed to children’s attention during SMSR, potentially making the word learning task more difficult. Discussion The findings of this study have implications for how to approach shared reading with young children in new contexts with the use of emerging technology. We raise future research questions for a better understanding of best practices for screen mediated shared reading.